Виктор Васнецов: альбом / [Авт. текста Элеонора Пастон] (Мастера живописи, 2001)
Экземпляры: (20180514) / Инвентарный номер: 28565 / Цена: / Сис.шифр: 85.143(2Рос=Рус)5-8 Васнецов / Авт.знак: В19 / ГРНТИ: 18.31 / ББК: 85.143(2Рос=Рус)5-8 Васнецов я6